Composition and structure of Ti–Al alloy powders formed by electrochemical co-deposition in KCl–LiCl–MgCl2–TiCl3–AlCl3 molten salt. (December 2021) - Zhua, Fuxing; Li, Kaihua; Song, Wenchen; Li, Liang; Zhang, Dafu; Qiu, Kehui
Abstract: Direct electrochemical deposition from titanium and aluminum chlorides is a green and short process for preparing Ti–Al alloy powders, thereby relevant for replacing the conventional smelting process characterized by intermittent and high production costs. However, the morphologies and compositions of resulting Ti–Al alloy powders have not yet been systematically studied. Here, Ti–Al alloy powders with different compositions and morphologies were successfully prepared from a molten KCl–LiCl–MgCl2 salt containing AlCl3 and TiCl3 under different electrodeposition parameters. The electrochemical behaviors of Ti and Al ions were examined on Mo and Al working electrodes by cyclic voltammetry at different temperatures. The results revealed variable numbers of redox peaks with temperature and working electrode material. The influences of the cathodic parameters on compositions and morphologies of Ti–Al alloy products studied through potentiostatic and galvanostatic electrolysis revealed that factors like cathodic potentials, initial current densities, and mole ratios of TiCl3 /AlCl3 greatly influenced the chemical compositions of Ti–Al alloy products except for temperatures. Also, phase compositions of Ti–Al alloy products were mainly controlled by the electrodeposition potentials and mole ratios of TiCl3 /AlCl3 . Meanwhile, the morphologies and particle sizes of Ti–Al alloy powders varied with temperature, current density, and electrolyte composition. In sum, these findings look promising for future formation of Ti–Al alloy powders for various uses. Graphical abstract: Image 1 Highlights: Ti–Al alloy powders with different compositions and morphologies were successfully prepared from a molten KCl–LiCl–MgCl2 salt containing AlCl3 and TiCl3 . The number of redox peaks of Ti–Al alloys varied with temperature and working electrode material. Factors like cathodic potentials, initial current densities, and mole ratios of TiCl3 /AlCl3 greatly influenced the compositions and morphologies of Ti–Al alloy products.